Kvantorinių žodžių all, any, every, each klausimu - Pilka, A. (Kalbotyra, 1976)
This paper presents a review of proposals to describe the meaning of the indefinite pronouns all, any, every, each with the help of logical operators – the universal and the existential quantifiers. To achieve a more adequate analysis of the words under consideration in all their realizations logical metalanguage must be enriched with new semantic elements.